Therapeutic Potential of Triptolide in Treating Bone-Related Disorders - Gang, Wu; Hao, Hu; Yong, Huang; Ruibing, Feng; Chaowen, Li; Yizheng, Huang; Chao, Li; Haitao, Zhang (Frontiers in Pharmacology, 2022)
Triptolide, a diterpene triepoxide, is a pharmacologically active compound isolated from a Chinese medicinal herb, Tripterygium wilfordii Hook. F. (TwHF). Triptolide has attracted considerable interest in recent times due to its multiple biological and pharmaceutical activities with an emphasis on therapeutic importance in the treatment of diverse disorders. With essential medicinal implication, TwHF’s extract have been used as anti-inflammatory, ant-proliferative, anti-oxidative, and immunosuppressive agents for centuries with continuous and relevant modifications to date to enhance its utility in several diseases and pathophysiology. Here in this review, we accentuate the studies, highlighting the effects of triptolide in bone-related disorders both inflammatory and cancers particularly osteosarcomas and their manifestations. Based on this review, future avenues could be estimated for the potential research strategies, molecular mechanisms, and outcomes that might contribute to reinforce the new dimensions in the clinical applications of triptolide in bone-related disorders.